A revised approach to testing for asymmetric intermarket spillover effects - Najib Shrydeh; Mohammed Shahateet; Suleiman Mohammad; Mohammad Sumadi (Cogent Economics & Finance)
This paper applies a modified DCC framework to test for asymmetric intermarket spillover effects from the US to a sample of G7 stock markets following the outbreak of the COVID-19 pandemic. The adjustment proposed in this research article addresses the shortcomings associated with the methodologies developed by, inter alia, Forbes and Rigobon (2002). The results demonstrate that spillover is less likely to propagate across highly developed and firmly integrated financial markets.